Number Sense and Integers - Kashyap, Neha (Voices of Teachers and Teacher Educators, 2019)
This paper argues that a lot can be understood about the difficulties children have in studying mathematics by looking at their responses to worksheets or other given tasks carefully. It suggests a programme of teaching that focuses on concepts and engagement with abstractions, problem solving, logic and other capabilities in an hierarchical manner as is required by mathematics.